Some aspects of legal regulation of the budgetary systems of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
This paper considers the legal aspects of the budget system of the Republic of Kazakhstan. Based on the opinion of Kazakhstan and Russian scientists were the conclusions and suggestions. The article examines the issues of functioning of the budgetary system in the Republic of Kazakhstan, the main stages of the budget process.Key words: budget, budget system, budget process, budget procedures, the state budget.